KNOWLEDGE AND ATTITUDE REGARDING EPILEPSY AMONG NURSES IN ASUTIFI NORTH DISTRICT - Asare, Richard Opoku; Boakye, Akwasi; Aryee, Paul Armah (European Journal of Health Sciences, 2020)
Background: Epilepsy is one of the world's oldest known brain disorders among several medical conditions. A recent study has indicated that 70 million people are estimated to suffer from this disease. Despite the increase education and health care, some health professionals continue to linger in darkness about cause and treatment options of the disease. Purpose. The main objective of this study was to assess the knowledge and attitude regarding epilepsy among nurses within the Asutifi North District with the aim of understanding their subjective experiences and knowledge on epilepsy in a socio-cultural context and how their attitude shaped their practice towards people with epilepsy. Methodology. The study employed an exploratory descriptive cross-sectional design with 102 participants using a standard statistical formula. Data was collected using a paper based semi-structured self-administered questionnaire and analysis was by STATA version 12. Results. Findings showed that 67.7% (69/102) of the nurses were aware of the causes of epilepsy whereas 59.8% have low level of knowledge on the disease. Results indicated that 82.4% of the nurses suspect PWE have mental illness, 70.6% of the nurses had positive attitude towards epilepsy. The socio-demographic characteristics of religion (Muslim) (p=0.017), area of speciality (RMN) (p=0.045) as well as close family relationship with epilepsy (p=0.001) were significantly associated with knowledge on epilepsy. Factors that were found to influence attitude towards epilepsy were sex (Female) (p=0.037) and religion (Muslim) (p=0.012). However, specialty area (RMN) (p=0.054) did not statistically impact on the study. Nurses at the Asutifi North District therefore tended to have low knowledge and positive attitude on epilepsy. It is important to improve training and health care delivery for epilepsy. Recommendation. The Ghana Health Service in collaboration with the Ministry of Health should run intermediary workshops, at least every six months, to train nurses in epilepsy diagnoses to reduce the treatment gap. The health directorate should raise awareness and educate the communities on epilepsy to reduce stigma. Enhancing nursing education and training on epilepsy by the Ministry of Health and its agencies is imperative to improving health care delivery for people living with the disease